Optimal linear control driven for piezoelectric non-linear energy harvesting on non-ideal excitation sourced - Da Costa Ferreira, Douglas [UNESP]; Chavarette, Fábio Roberto [UNESP]; Peruzzi, Nelson José [UNESP] (Trans Tech Publications, 2014)
Non-linear energy harvesting system was project to enhance interaction to ambient vibration that is wide band and low power which difficult the design for resonant solution. To improve efficiency of a non-linear design it was project a control system based in optimal linear control (OLC). Applying numerical evaluations it was possible to analyze the kinetic energy from the system as also the resulting output voltage. As main result there was a considerable increase of output voltage due controlled system in comparison to open loop for the same excitation. © (2013) Trans Tech Publications, Switzerland.
Keywords: Efficiency; Energy harvesting; Non-ideal excitation; Non-linear model; Optimal linear control